The mediating effects of organizational learning orientation on the relationship between strategic management accounting information use and organizational performance / Jamaliah Said …[et al.] - Said, Jamaliah; Wee, Shu Hui; Othman, Rohana; Taylor, Dennis (Universiti Teknologi MARA Cawangan Selangor, 2010)
The use of strategic management accounting information is a key ingredient for organizational success. However, past literature suggests that examining the direct effects of strategic management accounting information use and organizational performance provides an incomplete picture. Several studies suggest that the use of strategic information enhances organizational performance through organizational learning orientation. However, the focus of past studies was not on strategic management accounting (SMA) information. In addition, it is unclear as to whether the use of strategic management accounting information could have a positive impact on organizational learning orientation which in turn enhances the performance of local government authorities (LGAs) in Malaysia. Hence, this study empirically examined the mediating effect of organizational learning orientation on the relationship between the SMA information use and organizational performance. Using data collected from 109 LGAs in Malaysia, the result supports the positive direct effect of SMA information use and organizational performance. Further analysis of mediating effect of learning orientation suggests that higher usage of SMA information is one of the support mechanism for organizational learning in response to the information generated. Subsequently, an organization learning enhances their ability to respond to changes in the environment which in turn contributes to better financial and service quality performance. For managers of Malaysian LGAs, the findings of the study suggest that the use of SMA information and learning orientation are an important mechanism to improve the level of financial and service quality performance.